3D Printing for Tissue Engineering Applications - Hacioglu, Askican; Yilmazer, Hakan; Ustundag, Cem Bulent (GAZI UNIV, 2018)
The goal of tissue engineering is to create functional tissues and organs for regenerative therapies, and total organ transplantation. Bioprinting tissues are one of the most attractive approaches for tissue engineering and regenerative medicine fields. Fabrication of a complex structure via bioprinting requires layer-by-layer fabrication strategy. Bioprinting is mainly based on three processes; imaging and computer aided the design of the tissue that we wanted to print, the production of bio-ink with the selection of proper substances, the choice of a proper bioprinter depending on the product that we want, for fabrication of scaffold and/or tissues. In recent years the 3D bioprinting technology has been developed and several approaches appear by the researchers. The approaches are biomimicry, autonomous self-assembly and mini-tissue building blocks. In this study, current and future potential applications of 3D printing for the tissue engineering and regenerative medicine will be discussed.
Keywords: Bioprinter; bioink; self-assembly; biomimicry; tissue engineering; FUTURE; BIOFABRICATION; PERSPECTIVES; DEPOSITION; Engineering